2013
DOI: 10.1111/geb.12067
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of the introduction of exotic and translocated species and future extirpations on the functional diversity of freshwater fish assemblages

Abstract: Aim To explore the effects of the introduction of exotic and translocated species and possible future extirpation of native species on the functional diversity (FD) of freshwater fish assemblages. Location Japanese archipelago. Methods We examined spatio‐temporal changes in species richness, FD, functional richness (the number of trait‐based functional groups), and the functional group composition between historical and current fish assemblages for 27 eco‐regions, and compared the relative effects of the intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(96 citation statements)
references
References 46 publications
6
86
1
Order By: Relevance
“…In support of this idea, Yamada et al (2011) concluded that the functional diversity of the macrocrustacean community in seagrass ecosystems is the variable at the local patch scale, but homogeneous (i.e., occurrence of functional redundancy) at the regional scale (e.g. Matsuzaki et al, 2013;Sasaki et al, 2014).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In support of this idea, Yamada et al (2011) concluded that the functional diversity of the macrocrustacean community in seagrass ecosystems is the variable at the local patch scale, but homogeneous (i.e., occurrence of functional redundancy) at the regional scale (e.g. Matsuzaki et al, 2013;Sasaki et al, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…By using groups and diversity based on ecological traits, i.e., ''functional group'' and ''functional diversity'', that is the value and range of functional traits and ecosystem function of organisms present in a community (e.g., Mouillot et al, 2013;Storkey et al, 2013), can lead to elucidate community assembly rules and/or ecosystem processes (Yamada et al, 2011;Matsuzaki et al, 2013;Sasaki et al, 2014). Functional diversity was measured based on the values and range of ecological traits of species such as microhabitat, dispersal ability, habitat type, life history, and trophic level (e.g., Schleuter and Daufresne, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the impact of this phenomenon has been the theme of several studies (Pinto-Coelho et al, 2008;Matsuzaki et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Current situation corresponds to present species composition, whereas historical situation refers to composition two centuries ago, that is, before human-induced changes in compositions through non-native introductions and extirpations of native species (Olden & Rooney, 2006). Although the patterns and determinants of changes in taxonomic similarity between assemblages from historical to current situation have been increasingly studied (Rahel, 2000;Olden & Poff, 2004;Leprieur et al, 2008b;Spear & Chown, 2008;Winter et al, 2009;Vill eger et al, 2011;Hermoso et al, 2012), much less attention has been devoted to future trends (but see Duncan & Lockwood, 2001;Olden & Poff, 2004;Olden et al, 2008a;Matsuzaki et al, 2013), especially at large spatial scales. Although the patterns and determinants of changes in taxonomic similarity between assemblages from historical to current situation have been increasingly studied (Rahel, 2000;Olden & Poff, 2004;Leprieur et al, 2008b;Spear & Chown, 2008;Winter et al, 2009;Vill eger et al, 2011;Hermoso et al, 2012), much less attention has been devoted to future trends (but see Duncan & Lockwood, 2001;Olden & Poff, 2004;Olden et al, 2008a;Matsuzaki et al, 2013), especially at large spatial scales.…”
Section: Introductionmentioning
confidence: 99%